Efficient separation method for treating high-talc-content and high-sulfur copper ore
The method addresses the challenge of talc and magnesium ion interference in high-talc-content high-sulfur copper ores by controlling slurry potential and using a mixed inhibitor to enhance copper recovery through pH adjustment and dispersant use, resulting in improved flotation efficiency.
Patent Information
- Application Number
- CN202411191865.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2025-01-03
AI Technical Summary
Existing methods for processing high-talc-content high-sulfur copper ores face challenges in effectively inhibiting talc and magnesium ions, which hinder the flotation of copper minerals, leading to low recovery rates and unstable flotation effects.
A method involving pH adjustment and dispersant use during grinding, followed by sequential addition of mixed depressants and collectors for copper priority flotation, combined with a mixed inhibitor to control slurry potential and inhibit talc, while regrounding middlings to enhance copper recovery.
The method effectively reduces the impact of magnesium hydroxide colloids and enhances talc inhibition, improving copper flotation recovery rates and stability by controlling slurry potential and using a mixed inhibitor to make talc hydrophilic, thereby optimizing the flotation process.
Smart Images

Figure CN119237158A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-sulfur ore flotation, in particular to a separation method for treating high-talc-content high-sulfur copper ore. Background Art
[0002] Copper is an important nonferrous metal and is widely used in electrical, light industry, machinery manufacturing, construction industry, national defense industry and other fields. It is an important basic raw material.
[0003] Dongguashan Copper Mine is a large-scale metamorphic primary copper sulfide deposit with strong hydrothermal alteration. The valuable metals are copper, sulfur, iron and associated gold and silver. The copper sulfide minerals in the ore are mainly chalcopyrite, which is closely related to the gangue, mainly inlaid with medium and fine particles, and the coarse, medium and fine particles are extremely unevenly distributed; the gangue minerals are mainly magnesium-containing silicates, especially talc, serpentine and other easy-to-float layered silicate gangue minerals; talc and serpentine are mostly associated together in the form of aggregates and have a close inlaid relationship. There is a lag in the flotation of copper minerals in the on-site production process, the recovery rate of rough copper is low, talc and pyrite are seriously accumulated in the middling ore, and the copper selection indicators fluctuate greatly.
[0004] Since the gangue minerals of Dongguashan Copper Mine are mainly magnesium silicates, the magnesium ion content in the pulp after grinding exceeds 500mg / L; after the mixing operation and the addition of lime, the upper layer of the pulp turns light green and contains fine flocculent colloids; the flocculent colloids are mainly magnesium hydroxide; the magnesium hydroxide colloid has a strong adsorption capacity, and its hydrophilic components hinder the adsorption of the collector on the surface of chalcopyrite, affecting the mineralization of chalcopyrite, resulting in the phenomenon of delayed floating of chalcopyrite. At the same time, talc has the characteristics of good floatability, easy grinding, and easy mudification. It is continuously circulated and accumulated in the process, affecting the floatability of copper minerals, deteriorating the flotation effect, and causing an increase in the consumption of flotation reagents.
[0005] There are two main methods for processing such high talc content and high sulfur copper ore:
[0006] One is pre-talc removal; before the flotation of copper sulfide, the talc that is very easy to float is removed in advance by adding a frother and using a flotation process to reduce the impact of talc on the flotation of copper minerals, which is conducive to improving the grade of copper concentrate. However, when the talc is removed by pre-floatation, some copper minerals with good floatability will float up, resulting in the loss of copper metal; generally, the corresponding process technology needs to be added to recover the lost copper minerals in the talc concentrate.
[0007] One is to directly inhibit talc; talc inhibitors are added during flotation to inhibit talc and make it enter the tailings. Talc inhibitors are divided into inorganic and organic types; inorganic inhibitors mainly include water glass, sodium hexametaphosphate, etc., and their inhibition mechanism is mainly that the substances formed after hydrolysis are adsorbed on the surface of talc, making the talc hydrophilic; organic inhibitors mainly include a large number of polymer inhibitors, such as CMC, guar gum, locust bean gum, sodium polyacrylate, dextrin, polyacrylamide, etc., which are used alone or in combination to selectively inhibit talc; but polymer inhibitors usually have poor solubility and are difficult to configure; excessive use of polymer inhibitors has a certain inhibitory effect on copper minerals, affecting the recovery rate of copper, increasing the viscosity of the slurry, easily deteriorating the flotation slurry environment, and affecting the sedimentation of the tailings; however, due to the good floatability of talc, it is often difficult to effectively inhibit it, the inhibition effect is unstable, and even has an adverse effect on the recovery of copper minerals with fine particle size. For example, Chinese invention patent publication number CN116618182A discloses an inhibitor for flotation separation of talc and chalcopyrite and its application, using welan gum as an inhibitor, and adding the inhibitor welan gum in roughing and concentrating operations.
[0008] The selection of this type of high-sulfur copper ore usually focuses on the inhibition of talc, while ignoring the influence of the slurry system (including slurry pH, magnesium ions, etc.) on the copper ore; therefore, how to reduce the influence of floating talc and magnesium ions after grinding on the flotation of copper minerals is one of the difficulties in the current mineral processing technology. Summary of the invention
[0009] In order to solve at least one of the above problems, the present invention provides an efficient separation method for processing high-talc-content high-sulfur copper ore.
[0010] The technical solution of the present invention is: S1. Potential control of raw ore pulp: directly add pH adjuster, activator and dispersant to adjust the pulp potential during grinding, grind the high talc content and high sulfur copper ore to -0.074 mm, accounting for 60% to 85% for standby;
[0011] S2. Copper priority flotation: The slurry after S1 slurry potential control is subjected to roughing and mixed depressants and copper collectors are sequentially added to perform preferential copper flotation. After one roughing and two scavenging, the copper rough concentrate and tailings are scavenged, and the intermediate ore is returned in sequence. The mixed depressant includes a composite polymer and a conventional polymer depressant in a ratio of 4:1;
[0012] S3. Copper rough concentrate beneficiation: The copper rough concentrate obtained by S2 rough separation is sequentially added with pH adjuster, dispersant and mixed inhibitor for two times of concentration to obtain copper concentrate and concentrated 1 tailings, and the middlings are returned in sequence;
[0013] S4. Regrinding of middlings: The tailings 1 from S3 and the concentrate 1 from S2 are combined and put into the middling regrinding, and the ore is ground to -0.045mm, accounting for 75% to 90%.
[0014] The high-sulfur copper ore with high talc content in S1 described in the above scheme has a Cu grade of >0.5%, an S grade of >10%, and a talc mineral content of >5%.
[0015] In the above scheme, the pH adjuster in S1 is one of lime and calcium hydroxide, and the pH is controlled to 10.5-11.0; the dispersant is one or more of sodium hexametaphosphate, sodium tripolyphosphate, and water glass, and the dosage is 200g / t-1200g / t; the copper activator is one or more of thiodiazole and benzotriazole, and the dosage is 50g / t-300g / t.
[0016] The composite high molecular polymer in the above scheme is polyaluminium chloride, polyaluminium sulfate or polyaluminium ferric sulfate, and the conventional high molecular inhibitor is CMC, guar gum or sodium polyacrylate.
[0017] The dosage of the mixed inhibitor in the above scheme is 100g / t to 500g / t.
[0018] The collector in S2 described in the above scheme is one or more of butyl xanthate, ethylthiocarbamate, 25# black medicine, and ethylthiocyanate, and the dosage is 30g / t to 100g / t.
[0019] In the above scheme, the pH adjuster in S3 is one of lime and calcium hydroxide, and the pH is controlled to 11.5-12.0; the dispersant is one or more of sodium hexametaphosphate, sodium tripolyphosphate, and water glass, and the dosage is 50g / t-300g / t; the dosage of the mixed inhibitor is 50g / t-200g / t.
[0020] The beneficial effects of the present invention are as follows: 1. For high-talc-content high-sulfur copper ores, the above technical solution is adopted to directly add lime or calcium hydroxide during the grinding and dissociation process to effectively remove magnesium ions. The strong impact force during grinding prevents the generated magnesium hydroxide from forming colloid, thereby solving the problem that the magnesium hydroxide colloid hinders the adsorption of the collector on the surface of the chalcopyrite, causing the chalcopyrite to float lagging;
[0021] 2. For high-talc-content and high-sulfur copper ores, the above technical solution is adopted. During the grinding and dissociation process, the pH adjuster and dispersant are directly used to control the slurry potential, reduce the potential difference between talc, serpentine and chalcopyrite, reduce the "heterogeneous coagulation" phenomenon, and reduce the formation of sludge cover on the surface of copper minerals by dispersing the talc after mudification, thereby providing favorable conditions for the flotation of copper minerals;
[0022] 3. For high-sulfur copper ore with high talc content, the above technical solution is adopted to add a mixed inhibitor of a composite polymer and a conventional polymer inhibitor, which combines the advantages of the traditional aluminum salt water glass method and conventional polymer (such as CMC, guar gum and sodium polyacrylate, etc.) inhibitors to inhibit talc. The aluminum salt polymer and the polymer react in advance to form a special molecular structure, which is adsorbed to the surface of the talc to make the talc surface hydrophilic and achieve the effect of efficiently inhibiting talc. By using aluminum salt polymers, the amount of inhibitors added can be reduced;
[0023] 4. For high-sulfur copper ores with high talc content, the above technical solution is adopted to add a mixed inhibitor of a composite polymer and a conventional polymer inhibitor. By using an aluminum salt polymer, the amount of the mixed inhibitor can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the process of the present invention;
[0025] Figure 2 It is a schematic diagram of the action of the composite polymer inhibitor in the present invention. DETAILED DESCRIPTION
[0026] The following is combined with Figure 1-Figure 2 , the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0027] Embodiment 1:
[0028] The processed high talc content high sulfur copper ore composition: Cu 0.81%, S19.37%; talc mineral content 5.53%, serpentine mineral content 4.67%. The copper in the ore is mainly copper sulfide, a small amount of tetrahedrite and black copper ore, and the copper oxidation rate of the ore is 3.28%.
[0029] In order to find out the main components of the difficult-to-select ions in the grinding slurry, deionized water was used for grinding, and the upper layer of the grinding slurry after precipitation was taken for water quality analysis. The analysis results are shown in Table 1. The results show that the pH of the slurry after grinding is 7.46, the magnesium ion content exceeds 500 mg / L, and the sulfate content is close to 3000 mg / L.
[0030]
[0031] Table 1 Grinding slurry water quality analysis results
[0032] Lime or calcium hydroxide is generally used to suppress sulfur in high-sulfur copper ores. The addition position of calcium hydroxide was compared. One was added during the grinding operation, and the other was added during the stirring operation after the grinding. The upper layer of the slurry after precipitation was taken for water quality analysis. When added during the grinding operation, the upper layer of the slurry was clear and transparent, while when added during the stirring operation, the upper layer of the slurry was light green and contained fine flocculent colloids, which were magnesium hydroxide. The water quality analysis results are shown in Table 2. The results show that the addition of calcium hydroxide during the grinding operation and the stirring operation can effectively reduce the Mg content in the water. 2+ With SO4 2- Concentration, the addition of calcium hydroxide in the grinding operation effectively prevents the generated magnesium hydroxide from forming colloid through the strong impact force of grinding.
[0033]
[0034] Table 2 Analysis results of water quality of the upper layer of grinding slurry at different calcium hydroxide addition positions
[0035] For the above-mentioned high-talc and high-sulfur copper ore, fixed flotation reagent conditions were used to compare the flotation effects of copper minerals at two calcium hydroxide addition positions. The test process consisted of one roughing and one scavenging. The test results are shown in Table 3.
[0036]
[0037] Table 3 Calcium hydroxide addition position test results
[0038] The results show that when calcium hydroxide is added in the roughing stirring operation, the roughing copper recovery rate is low and the copper mineral shows obvious hysteresis phenomenon; when calcium hydroxide is added in the grinding operation, the flotation rate of copper mineral is significantly better than that of calcium hydroxide added in the roughing stirring operation, and the roughing copper recovery rate is greatly improved; this indicates that the strong impact force during grinding prevents the generated magnesium hydroxide from forming colloid, which solves the problem that the magnesium hydroxide colloid hinders the adsorption of the collector on the surface of chalcopyrite, causing the lagging flotation of chalcopyrite.
[0039] The talc inhibition principle of the present invention:
[0040] Talc (Mg 3 [Si 4 O 10 ](OH) 2 ) is a layered hydrated magnesium silicate mineral. During the grinding and dissociation process, the crystal structure is destroyed, forming two surfaces with different properties: the basal surface and the end surface. The basal surface is composed of non-polar bonds of tetrahedral silicon oxygen faces, has no polarity, and is hydrophobic. The end surface is mainly composed of unsaturated bonds formed by the breakage of Si-O and Mg-O(OH), and is hydrophilic.
[0041] First, sodium carboxymethyl cellulose and polyaluminium sulfate can be combined together through chemical reaction to form a unique molecular structure of sodium carboxymethyl cellulose-polyaluminium sulfate; when added to the slurry, the adsorption of sodium carboxymethyl cellulose-polyaluminium sulfate is enhanced, and the aluminum ions and hydroxyl polyaluminium ions are electrostatically adsorbed on the surface of talc, while the other end has a large number of hydroxyl groups with strong hydrophilicity, which enhances the hydrophilicity of talc; see the schematic diagram of the inhibition principle Figure 2 At the same time, sodium carboxymethyl cellulose itself can be adsorbed on the surface of talc through hydroxyl and carboxyl groups, and the addition of water glass and sodium hexametaphosphate increases the adsorption of carboxymethyl cellulose on the surface of talc, making it hydrophilic and playing an inhibitory role on talc.
[0042] For the above-mentioned high-talc-content and high-sulfur copper ore, fixed collector reagent conditions were used to compare the effects of different inhibitor types in inhibiting talc. The test process consisted of one roughing and one scavenging. The test results are shown in Table 4.
[0043]
[0044] Table 4 Test results of different inhibitor types
[0045] The results show that the mixed inhibitor of composite polymer and conventional polymer inhibitor has a significantly better inhibitory effect on talc than the traditional aluminum salt water glass method and conventional polymer method.
[0046] On the basis of the above-mentioned slurry control and talc suppression, the high talc content and high sulfur copper ore are subjected to the following process steps:
[0047] (1) Grinding: directly add 2000 g / t of calcium hydroxide (slurry pH 10.17), 300 g / t of sodium tripolyphosphate and 200 g / t of thiodiazole to control the slurry potential, grind the talc-containing high-sulfur copper ore to -0.074 mm, accounting for 71.32%, and set aside;
[0048] (2) After the slurry potential is regulated in step 1, 500 g / t of mixed depressant (polyaluminium sulfate: CMC = 4:1) is added to the slurry for roughing, and 60 g / t of collector (ethiocarbamate: 25# black medicine = 6:4) is added to perform copper preferential flotation. After one roughing and two scavenging, the copper rough concentrate and tailings are obtained for scavenging, and the middlings are returned in sequence;
[0049] (3) adding 600 g / t of calcium hydroxide (pH: 11.82), 100 g / t of sodium tripolyphosphate, and 100 g / t of a mixed inhibitor to the copper concentrate prepared in step 2 to obtain a copper concentrate and a tailings of the first selected product, and returning the intermediate ore in sequence;
[0050] (4) The middlings obtained in step 3 and the scavenging concentrate 1 obtained in step 2 are combined and put into the middlings for regrinding, and the ore is ground to -0.045 mm, accounting for 84.52%, and then returned to the roughing closed circuit;
[0051] Technical indicators: Final copper concentrate Cu grade: 19.15%, recovery rate: 86.14%.
Claims
1. An efficient separation method for treating high-talc-content high-sulfur copper ore, characterized in that The following steps are involved: S1. Potential regulation of raw ore pulp: pH adjuster, activator and dispersant are directly added to adjust the ore pulp potential during grinding, and high talc content and high sulfur copper ore are ground to -0.074 mm, accounting for 60% to 85% for standby; S2. Copper priority flotation: The slurry after S1 slurry potential control is subjected to roughing and mixed depressants and copper collectors are sequentially added to perform preferential copper flotation. After one roughing and two scavenging, the copper rough concentrate and tailings are scavenged, and the intermediate ore is returned in sequence. The mixed depressant includes a composite polymer and a conventional polymer depressant in a ratio of 4:1; S3. Copper rough concentrate beneficiation: The copper rough concentrate obtained by S2 rough separation is sequentially added with pH adjuster, dispersant and mixed inhibitor for two times of concentration to obtain copper concentrate and concentrated 1 tailings, and the middlings are returned in sequence; S4. Regrinding of middlings: The tailings 1 from S3 and the concentrate 1 from S2 are combined and put into the middling regrinding, and the ore is ground to -0.045mm, accounting for 75% to 90%.
2. The efficient separation method for treating high-talc-content high-sulfur copper ore according to claim 1, characterized in that: The high-sulfur copper ore with high talc content in S1 has a Cu grade of >0.5%, an S grade of >10%, and a talc mineral content of >5%.
3. The efficient separation method for treating high-talc-content high-sulfur copper ore according to claim 2, characterized in that: The pH adjuster in S1 is one of lime and calcium hydroxide, and the pH is controlled to 10.5-11.0; the dispersant is one or more of sodium hexametaphosphate, sodium tripolyphosphate, and water glass, and the dosage is 200g / t-1200g / t; the copper activator is one or more of thiodiazole and benzotriazole, and the dosage is 50g / t-300g / t.
4. The efficient separation method for treating high-talc-content high-sulfur copper ore according to claim 1, characterized in that: The composite high molecular polymer is polyaluminium chloride, polyaluminium sulfate or polyaluminium ferric sulfate, and the conventional high molecular inhibitor is CMC, guar gum or sodium polyacrylate.
5. The efficient separation method for treating high-talc-content high-sulfur copper ore according to claim 1, characterized in that: The dosage of the mixed inhibitor is 100 g / t to 500 g / t.
6. The efficient separation method for treating high-talc-content high-sulfur copper ore according to claim 1, characterized in that: The collector in S2 is one or more of butyl xanthate, ethylthiocarbamate, 25# black medicine, and ethylthiocyanate, and the dosage is 30g / t to 100g / t.
7. The efficient separation method for treating high-sulfur copper ore with high talc content as claimed in claim 1, characterized in that: The pH adjuster in S3 is one of lime and calcium hydroxide, and the pH is controlled to 11.5-12.0; the dispersant is one or more of sodium hexametaphosphate, sodium tripolyphosphate and water glass, and the dosage is 50g / t-300g / t; The dosage of the mixed inhibitor is 50g / t~200g / t.